RF Propagation Characteristics of Y-shaped Coupler for Millimeter-Wave Gyro-TWT - Akash A.; Thottappan M. (My University, 2025)
In this paper, the RF propagation characteristic of Y-shape input coupler for TE01 mode 92 GHz gyro-TWT is presented. The input coupler converts the fundamental rectangular TE10 mode into desired circular TE01 mode of gyro-TWT through a Y-shape power divider. The input TE10 mode is fed through the W-band rectangular waveguide (WR-10). A pill-box window is also used to isolate the vacuum inside the circuit from the outside atmospheric pressure. The CST simulation results predicts that input coupler offers a good transmission and low reflection (below-15 dB) over the frequency range of 88-100 GHz. © 2020 Indian Radio Science Society.